Effects of Rate of Drying, Life History Phase, and Ecotype on the Ability of the Moss Bryum Argenteum to Survive Desiccation Events and the Influence on Conservation and Selection of Material for Restoration - Greenwood, Joshua Lee; Stark, Lloyd R.; Chiquoine, Lindsay P. (Frontiers in Ecology and Evolution, 2019)
Desiccation stress is frequently experienced by the moss Bryum argenteum and can influence survival, propagation and niche selection. We attempted to disentangle the interacting factors of life history phase (five categories) and rate of desiccation (time allotted for induction of desiccation tolerance) for thirteen ecotypes of B. argenteum. Using chlorophyll fluorescence as a stress index, we determined how these parameters influenced desiccation tolerance. Rate of drying and life phase significantly affected desiccation tolerance. The reaction norms of desiccation tolerance displayed by the thirteen ecotypes showed a substantial degree of variation in phenotypic plasticity. We observed differences in survival and fluorescence between rapid and slow drying events in juveniles. These same drying applications did not produce as large of a response for adult shoots (which consistently displayed high values). Some juvenile and protonemal ecotypes, such as those from the southwest United States, possessed higher innate tolerance to rapid drying, and greater resilience compared to ecotypes sourced from mesic localities in the United States. These results show a complex nuanced response to desiccation with ecotypes displaying a range of responses to desiccation reflecting both inherently different capacities for tolerating desiccation as well as variation in capacity for phenotypic plasticity. Our results suggest that we should expect few short-term effects of climate change due to high desiccation tolerance of adult shoots, but significant adverse long-term effects on colony establishment due to low tolerance of protonema and juvenile shoots. Further, we would recommend that future studies using mosses for habitat restoration of aridlands consider the desiccation tolerance capacity of individual ecotypes used for cultivation and later re-introduction. Understanding how mosses respond to desiccation is essential to interpret ecological roles, habitat preferences, selective pressures, and responses to climate change, and to estimate the potential effects of climate changes on bryophyte species and populations.